FACTORS ASSOCIATED WITH VOLUNTARY BLOOD DONATION AMONG LIRA UNIVERSITY STUDENTS. CROSS-SECTIONAL STUDY. - Kayizzi, Julius; Opollo, Marc Sam; Puleh, Sean Steven; Kigongo, Eustes; Kabunga, Amir; Kisakye, Jovan; Kasaija, Deo; Khanakwa, Voni Alice; Lubangakene, Julius; Modi, Derick (Student's Journal of Health Research Africa, 2024)
Abstract According to UBTS, the total units of blood collected increased from 131,226 in 2007/2008 to 274,308 in 2018/19 but still less than the WHO recommendation of 1% of Uganda's population. To save the lives of patients due to accidents, obstetric and gynecological bleedings, cancers, and severe anemia with low blood volumes. This study will assess the factors associated with voluntary blood donation among Lira University students. Methodology A cross-sectional study using mixed methods of data collection was carried out among Lira University students. A sample size of 311 was calculated using the Yamane formula and recruited using a stratified random sampling technique and 5 key informants for qualitative data. SPSS version 20 was used for data entry and analysis. Univariate analysis was used to determine frequencies, proportions, and ranges. At bivariate analysis, a bivariate logistic regression was performed between the independent variables and dependent variable at a 95% confidence interval, Crude odds ratios (COR) were used as measures of association. Variables with P ≤0.05 were considered significant associations with the dependent variable. Results Their mean age was 23.7 years. The study population comprised approximately 40.5% blood donors of which 23.8% were blood donors. The majority of the participants (79.8%) had positive attitudes towards blood donation and the non-donors (61.7%) had never got a chance to donate. The majority of the respondents (59.5%) were male. Conclusion High awareness, influencing positive attitude, and regular blood donation drives should be prioritized if we are to achieve 1% donors of the population as recommended by WHO. Recommendation The Uganda Blood Transfusion Service should do more talk shows via announcements in public gatherings, and mouth-to-mouth engagements with the students, and handle first-time donors well to recruit and retain donors.